Framework para auxiliar terapeutas no design de recursos Audiovisuais para ensinar competências e habilidades a crianças autistas - Nóbrega, Rafael Moura Toscano da (2019)
Technology provides a myriad of resources to provide guidance and instructional support to the development of new skills and abilities. Within this scope, we can highlight the use of audiovisual and multimedia resources for teaching skills and abilities to children diagnosed with Autism Spectrum Disorder (ASD). This appropriation of technology establishes a scenario of media, interaction and learning, which is not currently supported by traditional theoreticalmethodological models of Communication, Computing and Pedagogy. Moving forward in this theme, this work proposes a framework with recommendations and visual resources to help the description, planning and production of audiovisual systems that potentiate the teaching strategies of the therapists. The framework, called Tuto Play, is proposed from the theoretical integration of Audiovisual Design to the Taxonomy of Educational Objectives studies. In this preposition, the child with Autistic Disorder is considered as an individual that in its totality assumes multiple levels of interaction with the media and that these can be understood and related to cognitive, affective and psychomotor domains. In addition, it is also understood that the use of media in this context is shared between professionals (clinical or educational) and responsible (family) in such a way that this factor should be considered by the content and pedagogical project offered. In addition to the recommendations for planning the educational objectives, the framework also offers a matrix with thirteen interaction formats and a use case to facilitate the understanding of the therapists of the practical application of Tuto Play. In order to validate the framework, a workshop was held with 28 therapists from the areas of psychology, psychopedagogy, pedagogy, speech therapy, occupational therapy, art therapy, and physical education, who work in a rehabilitation center for people with disabilities. In this workshop the experts knew, applied and evaluated the framework. In general, the participants received the framework positively, demonstrating also the ability to understand the application of the framework. Thus, research contributes to teaching strategies that integrate levels of interaction from cognitive, affective and psychomotor domains, which impact the generation of content and systems adaptive to the needs of the bearer.